Pineapple juice preservation by pulsed electric field treatment - Abu Yousuf; Md Anisur Rahman; M Rakib Uddin; Md Mozammel Hoque; A S M Sayem; Md Shahadat Hossain; Md Shah Ali; Md Sazzad Ahmed; Mushaida Haque (Open Journal of Biological Sciences - Peertechz Publications, 2020)
The effect of pulsed electric field (PEF) treatment on pineapple juice, applied in a batch system, was studied in terms of change in microbial community, bioactive compounds, and antioxidant capacity. Among the bioactive compounds, total phenolic content (TPC), flavonoid, ascorbic acid, and β-carotene content were evaluated. The results were monitored over a 10 days of storage at −20 ºC and compared with that of untreated juice sample. A PEF device-designed and fabricated in laboratory-was used for this purpose and the applied electric field strength were 9 kV/cm, 11 kV/cm, and 13 kV/cm at a frequency of 100 Hz. Highest microbial inactivation was observed at 13 kV/cm field intensity, which was the greatest possible field strength supplied by the PEF system. During storage, microbes grew in PEF treated juice, though at a slower pace than the untreated one, since the applied field intensity was far short of critical value to inactivate them entirely. All the bioactive compounds experienced a slight reduction in treated juice. Over time, the TPC and β-carotene of treated juice reduced at a slower rate than the untreated juice, whereas flavonoid and ascorbic acid content diminished at a similar rate. The treated juice lost its antioxidant capacity at a lower speed than the untreated one, though it did not change immediately after PEF treatment. Therefore, with higher electric field applied, PEF processing may be an effective preservation technique for pineapple juice in achieving sustainable shelf-life with uncompromised nutritious and ant-oxidant values over long term storage.